Lack of collagen α6(IV) chain in mice does not cause severe-to-profound hearing loss or cochlear malformation, a distinct phenotype from nonsyndromic hearing loss with COL4A6 missense mutation. - Shaoying Tang; Tomoko Yonezawa; Yukihide Maeda; Mitsuaki Ono; Takahiro Maeba; Toru Miyoshi; Ryusuke Momota; Yasuko Tomono; Toshitaka Oohashi (PLoS ONE)
Congenital hearing loss affects 1 in every 1000 births, with genetic mutations contributing to more than 50% of all cases. X-linked nonsyndromic hereditary hearing loss is associated with six loci (DFNX1-6) and five genes. Recently, the missense mutation (c.1771G>A, p.Gly591Ser) in COL4A6, encoding the basement membrane (BM) collagen α6(IV) chain, was shown to be associated with X-linked congenital nonsyndromic hearing loss with cochlear malformation. However, the mechanism by which the COL4A6 mutation impacts hereditary hearing loss has not yet been elucidated. Herein, we investigated Col4a6 knockout (KO) effects on hearing function and cochlear formation in mice. Immunohistochemistry showed that the collagen α6(IV) chain was distributed throughout the mouse cochlea within subepithelial BMs underlying the interdental cells, inner sulcus cells, basilar membrane, outer sulcus cells, root cells, Reissner's membrane, and perivascular BMs in the spiral limbus, spiral ligament, and stria vascularis. However, the click-evoked auditory brainstem response analysis did not show significant changes in the hearing threshold of Col4a6 KO mice compared with wild-type (WT) mice with the same genetic background. In addition, the cochlear structures of Col4a6 KO mice did not exhibit morphological alterations, according to the results of high-resolution micro-computed tomography and histology. Hence, loss of Col4a6 gene expression in mice showed normal click ABR thresholds and normal cochlear formation, which differs from humans with the COL4A6 missense mutation c.1771G>A, p.Gly591Ser. Therefore, the deleterious effects in the auditory system caused by the missense mutation in COL4A6 are likely due to the dominant-negative effects of the α6(IV) chain and/or α5α6α5(IV) heterotrimer with an aberrant structure that would not occur in cases with loss of gene expression.